1991
DOI: 10.2307/3536800
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Trace Elements and Organochlorines by Surf Scoters Wintering in the Pacific Northwest

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…It is interesting to briefly note that for this study, the hepatic trace element data of combined fish species (which are not explored in detail in this work), the nearest neighbor cluster correlation to selenium is also manganese. A Mn-Se correlation has been previously observed in male surf scoter livers in the U.S. Pacific Northwest [47], although similar work examining white-winged scoters in Alaska did not detect this relationship [48].…”
Section: Cd-mn-se-hg-as Clustermentioning
confidence: 72%
“…It is interesting to briefly note that for this study, the hepatic trace element data of combined fish species (which are not explored in detail in this work), the nearest neighbor cluster correlation to selenium is also manganese. A Mn-Se correlation has been previously observed in male surf scoter livers in the U.S. Pacific Northwest [47], although similar work examining white-winged scoters in Alaska did not detect this relationship [48].…”
Section: Cd-mn-se-hg-as Clustermentioning
confidence: 72%
“…In the Aleutian Islands, several studies have demonstrated high THg concentrations in birds with concentrations sometimes increasing westward across the island chain (Anthony et al, 2007; Ricca et al, 2008). In Washington’s Puget Sound, surf scoters exhibited THg concentrations similar to those of surf scoters in San Francisco Bay, California (Henny et al, 1991; Ohlendorf et al, 1987) and mercury concentrations of both surf scoters and western grebes increased as they over-wintered in Puget Sound (Henny et al, 1991, 1990). The hotspot in the Gulf Coast of Texas included Lavaca Bay, a designated mercury superfund site.…”
Section: Resultsand Discussionmentioning
confidence: 99%
“…In some cases, Surf Scoters display clear specialization on bivalves, particularly mussels (Vermeer 1981, Lacroix 2001. However, while specialization on bivalves appears seasonally stable for White-winged Scoters, diet patterns often change for Surf Scoters when they forage for prey at greater depths (S. sicarius bivalves) and for foods with seasonal availabilities that are either predictable (herring spawn, eelgrass epifauna) or unpredictable (commercial grain, reproducing polychaetes; Henny et al 1991, Lacroix et al 2005. Our diet estimates within Birch Bay indicate that Surf Scoters consume more nonbivalve prey than do Whitewinged Scoters.…”
Section: Discussionmentioning
confidence: 97%